1993
DOI: 10.1095/biolreprod49.6.1202
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-Associated Proteins in Holstein Bull Seminal Plasma1

Abstract: This study was undertaken to determine whether bovine seminal plasma contained protein markers associated with bull fertility, and whether these markers were of value in predicting bull fertility. Seminal plasma was obtained from 35 Holstein bulls of known fertility. Two-dimensional PAGE of seminal plasma samples indicated that two proteins (26 kDa, pI 6.2; 55 kDa, pI 4.5) predominated in higher-fertility bulls, and two proteins (16 kDa, pI 4.1; 16 kDa, pI 6.7) predominated in lower-fertility bulls. Densitomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
233
1
18

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(264 citation statements)
references
References 30 publications
12
233
1
18
Order By: Relevance
“…Seminal plasma has an important role in maintaining sperm motility during storage in the oviduct and contains multiple proteins that are associated with bull fertility (Gwathmey et al 2006;Killian et al 1993). SVS8 was up regulated in R heifers compared with V heifers but the role of SVS8 in the endometrium at this stage of embryonic development is, as yet, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal plasma has an important role in maintaining sperm motility during storage in the oviduct and contains multiple proteins that are associated with bull fertility (Gwathmey et al 2006;Killian et al 1993). SVS8 was up regulated in R heifers compared with V heifers but the role of SVS8 in the endometrium at this stage of embryonic development is, as yet, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Yue et al (2009) também identificaram proteínas de 72, 37 e 18kDa associadas à alta viabilidade espermática, enquanto um fator de 15kDa foi associado à baixa viabilidade espermática em ovinos. Além disso, Killian et al (1993) correlacionaram o fator proteico de 26kDa à alta fertilidade em touros. Alvarez e Storey (1995) demonstraram que a Albumina presente no plasma seminal está envolvida tanto com a proteção da membrana plasmática quanto com a manutenção da motilidade, uma vez que essa proteína absorve o peróxido de lipídio, protegendo as células.…”
Section: Discussionunclassified
“…It is unclear whether the effect of processing that decreased the abundance of these BSP proteins by more than half would render them ineffective in preventing premature capacitation and acrosome reaction of sperm from normal fertility bulls in the female tract. Spot volume data indicated that removal of the major seminal plasma proteins exposed less abundant low molecular weight proteins like spermadhesins, especially spermadhesin Z 13 which has been identified as an antifertility factor [2,14] in bovine semi-nal plasma.…”
Section: Discussionmentioning
confidence: 99%